IRIDOIDS FROM PHLOMIS SEVERTZOVII AND ITS IMMUNOSTIMULATING AND ANTITOXIC ACTIVITY - Durbek Usmanov; Ugiloy Yusupova; Nurmurod Sheralievich Ramazanov; Kamal Dzhamalovich Kucherbayev (Academic Scientific Journal of Chemistry, 2019)
From the aerial parts of Phlomis severtzovii (Lamiaceae) growing in Uzbekistan, five known iridoid glycosides were isolated for the first time. On basis of UV, IR, 1 H and 12C NMR spectroscopy the isolated substances were identified as 6β-hydroxypolamid (1), loganin (2), pulchelloside (3), shanshiside methyl ester (4) and phlorigidoside С (5). Additionally, noticeable immunostimulating and antitoxic activity of the sum of iridoids and 6β-hydroxypolamid (1) were revealed.